Is this systematic enough? Systematicity and openness in the implementation phase of DBR - Introna, Silvia (EDeR. Educational Design Research, 2024)
Within Design Based Research (DBR), designing and implementing an intervention in order to improve an educational practice become part of the research process. This represents a unique feature of DBR. Though the innovative nature of DBR raises questions that have not yet been answered. This paper focuses on the extent to which systematicity, as principle of scientific research, and openness, as essential prerequisite of teaching practice, can be both fulfilled within the implementation phase of DBR studies. By presenting an investigation in the field of German as a foreign language I will offer an example of the challenges that researchers face regarding the tension between systematicity and openness. Besides the discussion about DBR standards, the aim of this paper is to delineate concrete requirements for the further development of this research approach. Guidelines helping researchers to use DBR appropriately represent an important step which could clarify still controversial aspects of DBR and also lead to an increase in its use. In this paper, I suggest that concepts discussed within the implementation research, like for instance Fidelity of Implementation, can help to develop such guidelines.